إنشائية التفاصيل في الرواية الجزائرية المعاصرة مرايا الصالون لمحمود عياشي أنموذجا - سعدان, حسنة; عوادي, إيمان; ناني, أحلام (University of Eloued جامعة الوادي, 2024)
تقوم دراسة إنشائية التفاصيل في رواية مرايا الصالون لمحمود عياشي على تلك التفاصيل الدقيقة والجزيئيات المكونة لأسطر الرواية وأهميتها الكبيرة فيها، وسعينا للكشف عن أقنعتها وتبيين دلالاتها، حيث قامت الدراسة على فصلين؛ فصل تناولنا فيه إضاءات نظرية حول الرواية ونشأتها, وفصل ثاني تناولنا فيه إنشائية التفاصيل في الرواية, حيث فصلنا في كل من الشخصيات والأحداث والأمكنة والأزمنة, وقد جعل الروائي من التفاصيل مادة يبني عليها عالمه الروائي كما انه يتم تنسيقها فيكون صورا ومشاهد فائضة بالمعاني والدلالات الإيحاءات ووظفها توظيفا بارعا, مما يعطي لعمله الأدبي أو نصه السردي التجديد ومنح الشخصيات حيويتها. The study of the construction of in Mahmoud Ayachi's novel Mirrors of the Salon is based on those minute details and particles that make up the lines of the novel and their great importance in them, and we sought to reveal their masks and clarify their connotations, as the study was based on to chapters; A chapter in which we discussed theoretical insights about the novel and its origins, and second chapter in which we discussed the construction of details in the novel, where we discussed each of characters, events, places, and times. The novelist made the details a material on which he builds his fictional word, and they are also coordinated to form images and scenes filled with meanings, connotations, and suggestions, and he employs them. A skillful use that gives his literary work or narrative text renewal and gives the characters vitality.
أدب حديث ومعاصر
Keywords: الرواية; إنشائية; التفاصيل; الجزيئيات.; novel; structural; details; molecules.